Planting Axé in the City: Urban Terreiros and the Growth of Candomblé in Late Nineteenth-Century Salvador, Bahia, Brazil. (3rd May 2016) - Gordenstein, Samuel Lira
Abstract : Documentation from the second half of the nineteenth century suggests that Candomblé, the religion formed by African slaves and their descendants in Brazil, flourished in the crowded urban blocks of Bahia's capital city. Nonetheless, in contrast to some of the surviving, large congregations established in the sparsely populated outskirts of Salvador, very little is known about the spaces of worship located in the ground-level houses and basements where much of the city's Afro-Brazilian population lived. This article suggests that their existence hinged on an ability to neutralize the police repression and procure natural resources for ritual use. But even more so, their practices demanded access to the ground to "plant" the prerequisite materials underground before inaugurating the space for religious observations. Evidence from archaeological research in a late nineteenth-century house basement is presented to discuss the role played by buried "axés" in the religion. Ethnographic analogies with past and contemporary Candomblé practices are used to demonstrate continuities in the choice of locations and some of the characteristics of the objects whose roles were to protect the space and consecrate the soil for ritual practices.